Effects of tobacco seed oil methyl ester on performance and exhaust emissions of diesel engine - Parlak, A.; Karabas, H.; Ozsert, I.; Ayhan, V.; Cesur, I. (ELSEVIER SCI LTD, 2013)
Tobacco seed oil (TSO) was considered as a potential alternative fuel for compression ignition engines as the tobacco plant has high ecological tolerance and its farming can be realised on five different climatic regions in Turkey. In this study, the effects of TSO methyl ester (TSOME) on the performance and exhaust emissions of a single cylinder water cooled four-stroke diesel engine were experimentally investigated at full load conditions. The TSOME is mixed with diesel fuel in the mass rates of 10, 20, 50 and 100% (B10, B20, B50 and B100), and all the results tested with TSOME blends were compared with those of the standard diesel fuel. Comparing TSOME with standard diesel fuel, both the brake torque and the power of the engine were found higher 2.5% at B50. Hydrocarbon, CO and smoke emissions are measured lower, whereas the NOx emissions are found high.
Keywords: Tobacco seed oil; Transesterification; Biodiesel; Engine performance; Emission; COMBUSTION; YIELD; FUELS; Energy & Fuels